Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the equation [tex]\(\frac{y-2}{y+2} = \frac{y-5}{y+1} + 1\)[/tex], follow these steps:
1. Start with the given equation:
[tex]\[ \frac{y-2}{y+2} = \frac{y-5}{y+1} + 1 \][/tex]
2. Combine the terms on the right side of the equation into a single fraction:
[tex]\[ \frac{y-2}{y+2} = \frac{y-5 + (y+1)}{y+1} \][/tex]
Simplify the numerator:
[tex]\[ y-5 + y+1 = 2y - 4 \][/tex]
So the equation now becomes:
[tex]\[ \frac{y-2}{y+2} = \frac{2y-4}{y+1} \][/tex]
3. Clear the fractions by cross-multiplying:
[tex]\[ (y-2)(y+1) = (2y-4)(y+2) \][/tex]
4. Expand both sides of the equation:
[tex]\[ y^2 - y - 2y - 2 = 2y^2 + 4y - 4y - 8 \][/tex]
Simplify each side:
[tex]\[ y^2 - y - 2 = 2y^2 - 8 \][/tex]
5. Move all terms to one side to set the equation to zero:
[tex]\[ y^2 - y - 2 - 2y^2 + 8 = 0 \][/tex]
Simplify:
[tex]\[ -y^2 - y + 6 = 0 \][/tex]
Multiply through by -1 to make calculation easier:
[tex]\[ y^2 + y - 6 = 0 \][/tex]
6. Factor the quadratic equation:
[tex]\[ y^2 + y - 6 = (y+3)(y-2) = 0 \][/tex]
7. Set each factor equal to zero to solve for [tex]\(y\)[/tex]:
[tex]\[ y+3 = 0 \quad \text{or} \quad y-2 = 0 \][/tex]
Solving these gives:
[tex]\[ y = -3 \quad \text{or} \quad y = 2 \][/tex]
Therefore, the solutions to the equation [tex]\(\frac{y-2}{y+2} = \frac{y-5}{y+1} + 1\)[/tex] are [tex]\(y = -3\)[/tex] and [tex]\(y = 2\)[/tex].
1. Start with the given equation:
[tex]\[ \frac{y-2}{y+2} = \frac{y-5}{y+1} + 1 \][/tex]
2. Combine the terms on the right side of the equation into a single fraction:
[tex]\[ \frac{y-2}{y+2} = \frac{y-5 + (y+1)}{y+1} \][/tex]
Simplify the numerator:
[tex]\[ y-5 + y+1 = 2y - 4 \][/tex]
So the equation now becomes:
[tex]\[ \frac{y-2}{y+2} = \frac{2y-4}{y+1} \][/tex]
3. Clear the fractions by cross-multiplying:
[tex]\[ (y-2)(y+1) = (2y-4)(y+2) \][/tex]
4. Expand both sides of the equation:
[tex]\[ y^2 - y - 2y - 2 = 2y^2 + 4y - 4y - 8 \][/tex]
Simplify each side:
[tex]\[ y^2 - y - 2 = 2y^2 - 8 \][/tex]
5. Move all terms to one side to set the equation to zero:
[tex]\[ y^2 - y - 2 - 2y^2 + 8 = 0 \][/tex]
Simplify:
[tex]\[ -y^2 - y + 6 = 0 \][/tex]
Multiply through by -1 to make calculation easier:
[tex]\[ y^2 + y - 6 = 0 \][/tex]
6. Factor the quadratic equation:
[tex]\[ y^2 + y - 6 = (y+3)(y-2) = 0 \][/tex]
7. Set each factor equal to zero to solve for [tex]\(y\)[/tex]:
[tex]\[ y+3 = 0 \quad \text{or} \quad y-2 = 0 \][/tex]
Solving these gives:
[tex]\[ y = -3 \quad \text{or} \quad y = 2 \][/tex]
Therefore, the solutions to the equation [tex]\(\frac{y-2}{y+2} = \frac{y-5}{y+1} + 1\)[/tex] are [tex]\(y = -3\)[/tex] and [tex]\(y = 2\)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.